Mandatory disclosure regimes of domestic and international tax planning, background and impact in Europe and Latin America - Massy, Jessica (2021)
This article provides a brief overview of the exchange of information mechanisms between Tax Administrations, developed by the Organization for Economic Cooperation and Development (OECD) and the G20. Within this context it will be explained how the Report of Action 12 of the OECD/G20 project against base erosion and profit shifting (known as BEPS Project), influenced not only the European Union but also Latin America in the creation of potentially aggressive tax planning mandatory disclosure mechanisms. For this purpose, we will examine the most relevant aspects of the EU Directive 2018 (N° 822) of March 25, 2018 of the Council of the European or DAC6, as well as the mandatory disclosure regulations recently issued in Mexico and Argentina. The failed attempts by Brazil and Colombia to create this type of mechanisms will be explained as well.